PENGARUH PENAMBAHAN TEPUNG WORTEL (Daucus carota L.) PADA PEMBUATAN SOSIS IKAN GABUS (Ophiocephalus striatus) - Christiana Y. Singal; Erni J.N. Nurali; Teltje Koapaha; Gregoria S.S. Djarkasi (Universitas Sam Ratulangi, 2013)
ABSTRACTSausages is one of the food product made from ground meat mixed with spices and filled in long round casing. The aimed of this research were to (1). to obtain the exact mixed formula of carrot flour and cork fish in sausages processing, (2) to analyzed the chemical characteristics of sausages, and (3) to evaluate the sensory quality by panelists. The research was conducted at the Laboratory of Food Science and Processing, Faculty of Agriculturee Unsrat for 3 months. This research was designed using completely randomized design, with four treatments of mixed carrot flour and sago flourr , namely A= (2,5g carrot flour + 12,5g sago flour), B= (5g carrot flour + 10g sago flour), C= (7,5g carrot flour + 7,5g sago flour), D= (10g carrot flour + 5g sago flour). The result of Sensory evaluation showed that the most preferable treatment is fish sausages made of 10 g carrot flour and 5 g sago flour in 100 g cork fish. The result of cchemical analysis showed that the fish sausages contents 66,09% of moisture content, 2,7% of ash contented, 1,28 % fat content, 17,4 % protein content, and contained provitamin A.Keywords: Sausage, Carrot , Cork Fish